Hubungan Umur dan Jenis Kelamin dengan Pembesaran Tonsil pada Penderita Tonsilitis Kronis di RSUD dr. Rasidin Tahun 2018 - Nike Tamara; Irwan Triansyah; Rinita Amelia (Universitas Baiturrahmah, 2021)
Introduction: Chronic tonsillitis is an inflammation of the palatine tonsils whose complaints last more than 3 months. Chronic tonsillitis can be caused by regularly acute tonsillitis which causes tonsils permanent damage or this damage can occur if the medication is inadequate. The tonsils size and adenoids are small at <7 years old, increases in 7-15 years old and decrease in senility. Aims: To determine the relationship between age and gender with Tonsils enlargement in chronic tonsillitis patients of RSUD dr. Rasidin Hospital Padang in 2018. Method: This research is a qualitative analytic cross-sectional approach and uses a total sampling technique so that there are 70 patients with chronic tonsillitis obtained from the medical record data of RSUD dr. Rasidin Hospital Padang in 2018. The data obtained were analyzed using the SPSS program, which is the chi-square test. Result: The results showed that chronic tonsillitis sufferers by age were mostly in the 6-11 year old group as much as 26 patients (37.1%). Based on gender, most were found in women as much as 36 patients (51.4%). Based on the tonsils size, most of the T3-T3 size was 21 patients (30.0%). Based on the tonsil enlargement, most of the enlargement of tonsillar hypertrophy as many as 40 patients (57.1%). Conclusion: There was a significant relationship between age and enlargement of the tonsils (p = 0.046), and there was no significant relationship between gender and enlargement of the tonsils (p = 0.138) in patients with chronic tonsillitis in RSUD dr. Rasidin Hospital Padang in 2018.